Analysis of the Relationship of Parenting Parenting Patterns and Teacher Example with The Prosocial Behavior of Students - Apriono, Djoko; Sugiantoro , Achmad; Suttrisno, Suttrisno (Future Science / FSH-PH Publications, 2024)
The prosocial behavior of students in Cluster 05, Semanding District, Tuban Regency is still low. It is characterized by a lack of concern for the environment and other people. From the concern about this phenomenon, the researcher wants to examine more deeply about students' prosocial behavior. Researchers are trying to find a relationship between the level of prosocial behavior possessed by students and the upbringing and example of the teacher. This research is quantitative with a field survey method conducted on class VI students throughout Cluster 05 by means of random sampling based on Yaunt's theory of 10% for a population of 101-1000.